Dietary supplements and sports performance: Amino acids - Williams, M. (Journal of the International Society of Sports Nutrition, 2005)
This is the third in a series of six articles to discuss the major classes of dietary supplements (vitamins; minerals; amino acids; herbs or botanicals; metabolites, constituents/extracts, or combinations). The major focus is on efficacy of such dietary supplements to enhance exercise or sport performance.